The practice of texts : education and healing in south India - Cerulli, Anthony Michael (University of California Press, 2021)
"The Practice of Texts examines the uses of the Sanskrit medical classics in two educational institutions--the college and the gurukula--of India's classical life science, Ayurveda. In this interdisciplinary study, Anthony Cerulli probes late- and post-colonial reforms in ayurvedic education, the development of the ayurvedic college, and the impacts of the college curriculum on the ways that ayurvedic physicians understand and use the Sanskrit classics in their professional work today. His fieldwork in south India illuminates the nature of philology and ritual in the ayurvedic gurukula, and showcases how knowledge is exchanged between students, teachers, and patients. The result, Cerulli shows, is that the Sanskrit classics are presented and applied differently in the college and gurukula, producing a variety of relationships with these texts among practitioners and prompting a wide range of professional commitments and expectations. By interrogating the politics surrounding the place of the Sanskrit classics in ayurvedic curricula, the book reveals a spectrum of views about the history and tradition of Ayurveda in modern India"--